Aplikasi Metoda Elemen Hingga Dengan Algoritma Crank-Nicolson Dalam Penyelesaian Persamaan Difusi Panas Untuk Pembuatan Sel Surya Silikon Amorf (a-Si) Terpadu - Ridwan Abdullah Sani; M. Barmawi; Toto Winata; Sukirno Sukirno (Jurnal Matematika & Sains, 1996)
The solution of thermal diffusion equation computed numerically by finite element method is used to determine optimum conditions of laser irradiations in the solar cell fabrication. Structure discretization is analyzed in axisymmetric triangular ring elements. The program are codes in written using Fortran 77 language. The Crank-Nicolson algorithm and Fortran 77 IMSL library were used in solving stiffnen matrix equations of the structure. The convergence of the results are shown 50, 98, and 140 elements. The temperature distribution of at the center of laser beam in the all three layers of a-Si solar cells is also shown and superior compared with that of Kishi et al [19].